Methods of testing refractory materials Mouldable and castable refractories (BSI, 1967)
Refractory materials, Refractories, Testing, Thermal measurement, Water content determination, Crushing tests, Moisture measurement, Modulus of rupture, Spalling, Shaped refractories, Breaking load, Elastic constants, Specimen preparation, Sampling methods, Mechanical testing, Moulded materials, Dimensional changes, Compression testing, Heating tests, Compaction tests, Thermal testing, Workability, Dimensional measurement, Porosity measurement, Length measurement, Density measurement, Thermal conductivity, Thermal-shock tests, Thermal-cycling tests